A. A. Olizarowsky and His “Political Community of People” - Valkūnas, Leonas (Problemos, 1978)
A. A. Olizarowsky was professor at Vilnius University. In his book “Political Community of People” he quotes 254 authors, thus proving a great erudite. His world outlook, however, is rather eclectic. A realistic picture of life in the Polish-Lithuanian State including the author’s views on children’s education is presented in the book. Original and progressive ideas on a number of problems arresting the attention of the then society are expressed.